2019
DOI: 10.1101/679878
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights from a general, full-likelihood Bayesian approach to inferring shared evolutionary events from genomic data: Inferring shared demographic events is challenging

Abstract: Factors that influence the distribution, abundance, and diversification of species can simultaneously affect multiple evolutionary lineages within or across communities. These include environmental changes and inter-specific ecological interactions that cause ranges of multiple, co-distributed species to contract, expand, or become fragmented. Such processes predict genetic patterns consistent with temporally clustered evolutionary events across species, such as synchronous population divergences and/or change… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 79 publications
(128 reference statements)
1
11
0
Order By: Relevance
“…S4, S5). Thus, we recommend that future studies employ larger, multi‐locus datasets that allow divergence times and demographic changes to be reconstructed with greater power and resolution (Oaks, L’Bahy, L’Bahy, & Cobb, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…S4, S5). Thus, we recommend that future studies employ larger, multi‐locus datasets that allow divergence times and demographic changes to be reconstructed with greater power and resolution (Oaks, L’Bahy, L’Bahy, & Cobb, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we have found this method maintains good performance over a diverse range of situations where phylogenetic structure is produced, including differential transmission rates, epidemiological outbreaks, evolution of beneficial mutations, and differential sampling patterns. Our work is related to the research on species delimitation methods (see for example (Zhang et al 2013)) although targeted at within-species variation, and is also related to recent work on methods for detecting co-diversification of species(Oaks et al 2019). This method appears relatively robust compared to other methods against false-positive identification of phylogenetic structure, but nevertheless has good sensitivity for detecting structure in most situations.…”
Section: Discussionmentioning
confidence: 99%
“…The program thus estimates the timing of demographic events, as well as effective population sizes of ancestral and contemporary populations (which are used to infer shifts in population size). To generate input files for each dataset, we included the full alignments for each locus; Oaks, L’Bahy, and Cobb (2019) showed that using all sites substantially improves estimates of demographic event times. We separated each alignment into northern and southern populations for each species based on clustering analyses (Figure 2) for a total of six populations being compared by ecoevolity.…”
Section: Methodsmentioning
confidence: 99%